Luxury strategy of perfume brands in emerging markets: an exploratory study of luxury brands in the perfumes sector in Brazil - Paz, Julia Oliveira da (2016)
In recent years, emerging markets – considered the lead countries of the ‘developing world’ – have been outgrowing developed countries within the scope of the luxury market worldwide. Consequently, these new markets represent a promise, at the same time as a challenge to traditional luxury brands. According to Atwal and Bryson (2014), a significant increase in the consumer base of emerging markets coupled with the geographic shift in wealth allowed international luxury brands to enter 25 new markets in 2013 such as Brazil, India, Russia and China. Within this context, one of the challenges of the research will be to focus in one of the most significant emerging markets worldwide – Brazil – to be able to deeply understand the specificities of this market and the implications to the luxury strategy of perfume brands. In details, this research will also focus on the Brazilian perfumes sector. The main objective is to discuss how international luxury brands of the perfumes sector adapt their strategy given the complexities and specificities of the Brazilian luxury market and its perfumes sector. As an exploratory qualitative research, this study will analyse luxury brands of perfumes sector and their practices in Brazil from the managerial and strategic perspective. From the theory, the study will present two main perspectives on luxury strategy to, then, give an overview of the perfume sector within the Brazilian market and the specificities of the Brazilian consumer. Finally, the research will focus on the brands’ perspective to discuss how they adapt their strategies to this specific market and sector. For this approach, the methods will be in depth interviews with brands’ executives, complemented with archival research. By exploring a vague subject within a specific context from a new perspective than usually found in the existing literature, the main contribution of this research will be for managers and leaders of luxury perfume brands to use as a possible guideline of best practices of luxury strategy within this market. In other words, through the managerial and strategic perspective studied for each of the chosen brands, the result of this research will present similarities and divergences between theory and practice in order for these managers and leaders to acknowledge the challenges and specificities to be faced within the Brazilian luxury market and perfumes sector